THE INFLUENCE OF LIBRARY SERVICE QUALITY AND BOOK COLLECTION ON LIBRARY USERS’ READING INTEREST - Wahyuningtyas, Eni; Hiryanto, Hiryanto (Unversitas Muhammadiyah Mataram, 2026)
This study aims to analyze the influence of library service quality and book collections on user reading interest at the Public Library and Regional Archives Office in Malang City. The research method used was quantitative with a correlational explanatory approach. Data collection was conducted through a survey using a Likert-type questionnaire with a 1–5 Likert scale distributed to 100 respondents who were active library members. The sampling technique used was the Slovin formula with a 10% margin of error. Validity and reliability tests were conducted to ensure the accuracy and consistency of the research instrument, while data analysis used classical assumption tests and multiple linear regression analysis.The results showed that, partially, service quality significantly influenced reading interest, with a t-value of 3.336 and a significance level of 0.001. This indicates that the better the librarian's service quality, the higher the user's reading interest. Meanwhile, book collections have a positive but insignificant influence on reading interest with a calculated t value of 1.128 and a significance of 0.262, which indicates that increasing the number and variety of collections has not significantly increased reading interest because the existing collections have not fully met the needs and preferences of readers. Simultaneously, both variables have a significant influence on reading interest with a calculated F value of 10.518 and a significance of 0.000 <0.05, which indicates that the better the quality of service and collection, the greater the increase in reading interest of library users